STRATEGI ELECTRONIC PUBLIC RELATIONS P.T. ISM BOGASARI FLOUR MILLS DALAM MENINGKATKAN BRAND AWARENESS - Ramadhan, Handharu Laksa; Handoko, Rudy; Wibowo, Judhi Hari (Universitas 17 Agustus 1945 Surabaya, 2016)
Technological developments in the aspect of communication and increasing competition,demand public relations to creatively invent and devise a strategy to communicate its brand throughthe internet. The existence and growth of PT. ISM Bogasari which is the largest wheat flour producerin Indonesia with a market share of 57% amid the development of communication technology andincreasing competition. Encourage interest in the author's research on public relations strategy PT.ISM Bogasari flour mills in meninggkatkan brand awareness. The theory used in this research ispublic relations management process Scot M Cutlip and Brand Awareness.Metode analysis used isMiles and models. Huberman. Based on the results of research conducted by the author, it can beconcluded that: lack of relationships with customers in and challenges of competitors becomes thebasis of the formation of the strategy. Through the medium of websites, twiter, facebook, you tube. PT.ISM Bogasari flour mills, assuring the market share on the product quality, by forming the productinformation into four major cyber media content, ie the content of recipes, tips content, content, SMEtestimony, and testimony BBC. Besides Markowitz such content, interactive (two-way communication)performed on twiter and facebook social media with the aim that the formation of relationships in thetarget market. Efforts mengeleloh social media and website in order to appear on the first page ofgoogle or yahoo search or a search feature on social media also carried out by third parties, so thatthe message continues to be seen by the target audience.Keywords: Strategi, Electronic Public Relations, Brand Awareness